PENGARUH SENAM HAMIL TERHADAP PENURUNAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER II DAN III DI PUSKESMAS KECAMATAN CIPAYUNG JAKARTA TIMUR - Wahyuningsih; Diah Warastuti; Dina Martha Fitri (STIKES MITRA RIA HUSADA, 2022)
Physical changes that occur in the second and third trimesters of pregnancy sometimes cause discomfort to the mother, one of which is lower back pain. The purpose of this study was to determine the effect of pregnancy exercise on reducing low back pain in pregnant women in the second and third trimesters of the Cipayung District Health Center. The population of this study were all patients at the Cipayung District Health Center with a sample of 20 respondents. This study was a quantitative pre-experimental study with a one group pretest- posttest design type. Retrieval of data using the Numeric Rating Scale. The analysis used was univariate and bivariate. The results showed that the p-value was 0.001 with the p value of this study showed the p value <α (0.05) which means that it has a very significant difference in value. So it can be concluded that H0 is rejected and H1 is accepted for the reduction of low back pain in pregnant women in trimesters II and III. It is recommended that pregnant women in the II and III trimesters do exercise so that the lower back will experience a reduction in pain where the mother can ask for information from health workers about how to do pregnancy exercise Keywords Pregnancy exercise, lower back pain, pregnant women in the II and III trimesters